Antimicrobial Peptides for Topical Treatment of Osteomyelitis and Implant-Related Infections: Study in the Spongy Bone - Melicherčík, Pavel; Nešuta, Ondřej; Čeřovský, Václav (Pharmaceuticals (Basel, Switzerland), 2018)
We examined the benefits of short linear α-helical antimicrobial peptides (AMPs) invented in our laboratory for treating bone infection and preventing microbial biofilm formation on model implants due to causative microorganisms of osteomyelitis. For this purpose, we introduced a model of induced osteomyelitis that utilizes human femur heads obtained from the hospital after their replacement with artificial prostheses. We found that the focus of the infection set up in the spongy part of this bone treated with AMP-loaded calcium phosphate cement was eradicated much more effectively than was the focus treated with antibiotics such as vancomycin or gentamicin loaded into the same cement. This contradicts the minimum inhibitory concentrations (MIC) values of AMPs and antibiotics against some bacterial strains obtained in standard in vitro assays. The formation of microbial biofilm on implants made from poly(methylmethacrylate)-based bone cement loaded with AMP was evaluated after the implants' removal from the infected bone sample. AMPs loaded in such model implants prevented microbial adhesion and subsequent formation of bacterial biofilm on their surface. Biofilms did form, on the other hand, on control implants made from the plain cement when these were implanted into the same infected bone sample. These results of the experiments performed in human bone tissue highlight the clinical potential of antimicrobial peptides for use in treating and preventing osteomyelitis caused by resistant pathogens.
Keywords: implant-related infections; osteomyelitis; antimicrobial peptides; bone cement; femur heads